Effect of peppermint essential oil and ultrasonication on microbiology evaluation and quality parameters of stored chicken meat - Ashraf, Nabeel; Arshad, Zunaira; Sami, Rokayya; Almehmadi, Awatif M.; Alsanei, Woroud A.; Bedaiwi, Ruqaiah I.; Kadi, Roqayah H.; Abu-Zaid, Abeer A.; Al-Dhumri, Sami A.; Abushal, Suzan A.; Helal, Mahmoud (Frontiers in Sustainable Food Systems, 2025)
Chicken meat is a highly perishable food item that provides an ideal environment for microbial growth, which can affect its quality under refrigeration. The objective of this study was to determine the effects of peppermint essential oil (PEO) and ultrasonication (US) on the quality of broiler chicken meat. A total of seven chicken meat samples (T0–T6) were used, where T0 served as the control sample and T1–T6 were treated with different PEO concentrations (0.5 and 1%). These samples were subjected to US at a frequency of 37 kHz (for durations of 2, 4, and 6 min) and a power level of 600 W. Then, the samples were vacuum-packed in polyethylene bags and stored at refrigerator temperature for 12 days. Physicochemical analysis [including thiobarbituric acid reactive substances (TBARS), total volatile basic nitrogen (TVBN), pH, and water holding capacity (WHC)], texture profile analysis (cohesiveness, hardness, and chewiness), and microbial analysis (TPC, E. coli, Salmonella, and coliform) were conducted at 0, 3, 6, 9, and 12 days. Compared to untreated samples, all treated samples exhibited a significant (p < 0.05) decrease in microbial counts during storage. Ultrasonication for 6 min combined with 1% peppermint oil resulted in a significant decrease in TVBN and TBARS, along with an increase in WHC and cooking yield of chicken meat during storage. The treated group showed a significant decrease in total plate count, Salmonella, coliform, and E. coli, with counts decreasing from 1.53–3.76 CFU/g, 1.21–1.99 CFU/g, 1.08–1.48 CFU/g, and 1.95–2.99 CFU/g, respectively. In contrast, the untreated group showed counts of 2.4–7.71 CFU/g, 3.56–5.61 CFU/g, 1.87–4.41 CFU/g, and 4.47–7.23 CFU/g, respectively, over 12 days of refrigeration at 4°C. The highest cooking yield was observed in T6 (74.86%), while the lowest was in the control sample T0 (72.45%) after 12 days of storage. These findings indicate that the T6 sample showed significantly enhanced quality attributes of treated chicken meat samples. These results showed that PEO and US were effective natural methods of meat preservation that ultimately benefit the meat industry in terms of improved product quality and safety.